2017
DOI: 10.1002/pbc.26779
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of plasminogen deficiency patients with fresh frozen plasma

Abstract: Congenital plasminogen (Plg) deficiency leads to the development of ligneous membranes on mucosal surfaces. Here, we report our experience with local and intravenous fresh frozen plasma (FFP). We retrospectively reviewed medical files of 17 patients and their eight first-degree relatives. Conjunctivitis was the main complaint. Thirteen patients were treated both with intravenous and conjunctival FFP. Venous thrombosis did not develop in any. Genetic evaluation revealed heterogeneous mutations as well as polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
(60 reference statements)
0
24
1
Order By: Relevance
“…Preliminary results of the latter trial showed an improvement or resolution of LG in three affected patients treated with intravenous Glu‐plasminogen replacement . The use of local and intravenous FFP has been recently reported in a series of 11 patients with plasminogen deficiency and ligneous conjunctivitis; the clinical response rate to FFP treatment was 72% …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary results of the latter trial showed an improvement or resolution of LG in three affected patients treated with intravenous Glu‐plasminogen replacement . The use of local and intravenous FFP has been recently reported in a series of 11 patients with plasminogen deficiency and ligneous conjunctivitis; the clinical response rate to FFP treatment was 72% …”
Section: Resultsmentioning
confidence: 96%
“…16 The use of local and intravenous FFP has been recently reported in a series of 11 patients with plasminogen deficiency and ligneous conjunctivitis; the clinical response rate to FFP treatment was 72%. 26 We designed a haematological protocol for our patient with LG based on a combination of FFP transfusion and enoxaparin as a prophylactic treatment for dental invasive procedures. Rationale of our choice was as follows: (a) to give a replacement therapy to correct congenital plasminogen deficiency; (b) to use an anticoagulant drug to prevent an excess of fibrin formation at a reduced dosage to avoid bleeding.…”
Section: (G) (H)mentioning
confidence: 99%
“…Indeed, impaired fibrinolysis caused by PLG deficiency should be corrected by correcting PLG deficiency with transfusions, thereby avoiding formation of new membranes. However, two patients in this study with therapy failure were those unable to receive FFP transfusion . It is clear that transfusion alone was not sufficient for resolution of existing developed membranes, and that traditional interventions including surgery, were required.…”
Section: Clinicolaboratory Features Of Our Patients Treated With Systmentioning
confidence: 83%
“…To the Editor: We read with interest the article by Kizilocak et al., which introduces fresh frozen plasma (FFP) transfusion as a new treatment approach for type 1 plasminogen (PLG) deficiency. Type 1 PLG deficiency is a rare systemic disease characterized by markedly impaired fibrinolysis leading to the formation of ligneous fibrin‐rich pseudomembranes on mucosa and recognized by the characteristic lesions and diagnostic laboratory findings.…”
Section: Clinicolaboratory Features Of Our Patients Treated With Systmentioning
confidence: 99%
See 1 more Smart Citation